Monitoring of the teaching-learning of computer architecture based on skills, learning styles and semantic elements - Torres Carrion, P. (2013)
New technologies in education has driven the development of many investigations into pedagogy, which has led to the emergence of new computing mechanisms that contribute to the improvement of education quality. This paper aims to contribute to a process that monitors the progress of skills through the identification of learning styles and semantic elements in order to identify problems in academic performance to students. The relationship between skills and the learning style of students will be conceptualized in an ontology, which present recommendations for academic advancement, and also generate alerts when students have problems in the learning process.